Strategy for Empowering Village-Owned Enterprises through Parson's Social System Approach - Ikhwansyah, Isis; Mulyati, Etty; Wiganarto, Tri Utomo (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research examines Talcott Parsons' Structural Functionalist method to empowering Village-Owned Enterprises. BUMDes' economic and social dynamics are understood using this method. The Parsonian social framework's adaption factors, goal attainment, integration, and delay are studied. This normative, philosophical, and analytical research examines social and legal theories to characterize BUMDes' role in village development. The descriptive analytical research technique reviews BUMDes-related legislation, regulations, and practical practices. Qualitative data analysis yields extensive Parsons' theory application results. The research found that BUMDes promotes inclusive and sustainable village development. BUMDes adapts its economic approach to the village's possibilities, such as agricultural or tourist development. BUMDes may boost village revenue by fostering productive companies, achieving objectives by improving community welfare. The integration component emphasizes village institution-community engagement for social stability. Latency involves BUMDes' attempts to conserve local culture to retain village identity throughout development. However, financing and institutional coordination concerns are typically major barriers. This research found that Parson's strategy may help BUMDes improve Indonesian communities' economic and social growth.